Chernikov’s p-groups and integral p-adic representations of finite groups - Gudivok , P. M.; Vashchuk , F. G.; Drobotenko , V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The connection is studied between Chernikov p-groups and integral p-adic representations of finite p-groups. A description is presented with a precision up to isomorphism of certain classes of Chernikov p-groups.